Long intergenic noncoding RNA 00908 promotes proliferation and inhibits apoptosis of colorectal cancer cells by regulating KLF5 expression. Issue 2 (6th July 2020) - Shan, Ti‐Dong; Tian, Zi‐Bin; Li, Qian; Jiang, Yue‐ Ping; Liu, Fu‐Guo; Sun, Xue‐Guo; Han, Yue; Sun, Li‐Juan; Chen, Li
Abstract: Long intergenic noncoding RNAs (lincRNAs) play a vital role in the occurrence and progression of cancer. The mechanism of lincRNAs in colorectal cancer (CRC) has not been fully elucidated. In this context, an integrated comparative long noncoding RNA (lncRNA) microarray technology was used to determine the expression profile of lncRNAs in CRC. The roles of LINC00908 are unclear. We found that LINC00908 was significantly upregulated in CRC. Inhibition of LINC00908 resulted in reduced cell proliferation and G1 cell cycle arrest, which was mediated by cyclin D1, cyclin‐dependent kinase 4, and phosphorylated retinoblastoma. Moreover, inhibition of LINC00908‐induced apoptosis through the intrinsic apoptosis signaling pathway, as shown by the activation of caspase‐9 and caspase‐3. Mechanistically, miR‐143‐3p directly bound to LINC00908. miR‐143‐3p expression was negatively correlated with LINC00908 expression in CRC tissue. Functional experiments revealed opposing roles for miR‐143‐3p and LINC00908, suggesting that LINC00908 negatively regulates miR‐143‐3p. Mechanistically, miR‐143‐3p directly targets LINC00908. The KLF5 inhibitor ML264 affected proliferation and apoptosis, indicating that LINC00908 may act as a competing endogenous RNA to facilitate the expression of the miR‐143‐3p target gene KLF5. Thus, LINC00908 has an important proliferative and antiapoptotic role in CRC by regulating the cell cycle and intrinsic apoptosis. LINC00908 could be a potential biomarker and a new therapeutic target for CRC. Abstract : The KLF5 inhibitor ML264 affected proliferation and apoptosis, indicating that LINC00908 may act as a competing endogenous RNA to facilitate the expression of the miR‐143‐3p target gene KLF5. Thus, LINC00908 has an important proliferative and antiapoptotic role in colorectal cancer (CRC) by regulating the cell cycle and intrinsic apoptosis. LINC00908 could be a potential biomarker and a new therapeutic target for CRC.